Peningkatan Civic Literasi dengan Memanfaatkan Literasi Digital Melalui Pendidikan Kewarganegaraan di Perguruan Tinggi - Widiatmaka, Pipit; Kurniawan, Itok Dwi (Jurnal Pekommas, 2023)
The reading index in Indonesia is still relatively low, so many students become victims of fake news that develops on social media. In addition, students have not been able to utilize digital technology and digital literacy optimally, which has implications for weak knowledge related to civic literacy. The research designs used are literature reviews and qualitative research types. The research method is literature, while the data collection technique uses document studies, and the data analysis used is content analysis. Civic literacy has an important role in facing the era of society 5.0, with the ability to greatly help students participate in realizing harmony in the lives of the nation and state. Society 5.0 has a tough challenge for higher education if each lecturer does not equip students with civic literacy skills. The strategy of strengthening civic literacy through digital literacy can be done effectively by implementing varied learning methods and using digital-based learning media. Through this, students will be interested in learning, considering that they are a digital native generation who cannot be separated from digital technology. Increasing civic literacy is very effective by utilizing digital literacy so that every student can adapt to the times, especially in the era of society 5.0.